A modification and regeneration method for waste activated carbon

By synergistic activation of waste activated carbon by zinc chloride and sodium thiocyanate, and composited with steel slag micro powder and ferrocene, combined with the use of self-made binders of sodium silicate and polyvinyl alcohol, the problem of insufficient adsorption and desorption capacity and compressive strength of waste activated carbon is solved, and efficient resource regeneration and recycling are achieved.

CN118767900BActive Publication Date: 2025-04-08NANXIONG RONGYUAN CLOTHING GARMENT CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411000961.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-25
Publication Date
2025-04-08
Estimated Expiration
2044-07-25

AI Technical Summary

Technical Problem

In the prior art, the adsorption and desorption ability of waste activated carbon is poor, and physical structure damage leads to a decrease in compressive strength, which affects the subsequent use effect.

Method used

By synergistic activation of waste activated carbon by synergistically activating zinc chloride and sodium thiocyanate, compounding with steel slag micro powder and ferrocene, and bonding with sodium silicate and polyvinyl alcohol homemade adhesive, a solid network structure is formed to enhance compressive strength.

Benefits of technology

It significantly improves the adsorption capacity and compressive strength of waste activated carbon, enhances its desulfurization and denitrification properties, extends the service life of activated carbon, and realizes the recycling of resources.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a modification and regeneration method of waste activated carbon, belonging to the technical field of activated carbon, and the method comprises the following steps: S1, preparing an intermediate material; S2, preparing modified carbon; S3, preparing an activated carbon product. The present invention adopts zinc chloride and sodium thiocyanate to synergistically activate the waste activated carbon, effectively activates and forms pores, and increases the active sites on the surface of the activated carbon. On this basis, it is compounded with steel slag micropowder and ferrocene, which effectively increases the adsorption capacity of the obtained activated carbon. Therefore, the activated carbon thus obtained has an excellent desulfurization and denitrification effect; in addition, the present invention also makes a self-made adhesive for the bonding of activated carbon, and polyvinyl acetate is added in the process of preparing the adhesive, and its certain bonding property increases the strength of the prepared adhesive; anhydrous borax is added to improve the density of the network structure in the system, and the adhesive and the activated carbon are cross-mixed to form a tight whole, thereby enhancing the compressive strength of the obtained activated carbon.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of activated carbon, and in particular relates to a modification and regeneration method of waste activated carbon. Background Art

[0002] With the acceleration of industrialization, environmental pollution problems are becoming increasingly serious, especially the emission of sulfur dioxide and nitrogen oxides has become the main factor affecting air quality. Activated carbon is a porous material. Because of its high specific surface area, rich pore structure and good adsorption performance, it is widely used in the fields of gas and liquid adsorption, purification and depollution. However, during the use of activated carbon, its adsorption capacity will gradually decrease with the accumulation of adsorbents until it can no longer meet the use needs. At this time, the activated carbon is regarded as waste treatment. If these waste activated carbons are not properly handled, they will not only cause waste of resources, but also may cause secondary pollution to the environment. In addition, these discarded activated carbons generally still contain a large amount of useful substances and have high regeneration and recycling value. Direct disposal will cause great waste of resources. Therefore, it is of great practical significance to develop a method that can effectively modify and regenerate waste activated carbon.

[0003] However, although the methods for regenerating waste activated carbon currently available on the market can restore the adsorption capacity of activated carbon, their adsorption and desorption capabilities are poor, and they often cause damage to the physical structure of activated carbon, resulting in a decrease in its compressive strength, which affects the subsequent use effect. Therefore, it is of great application value to develop a method that can effectively regenerate waste activated carbon and simultaneously improve its compressive strength and desulfurization and denitrification performance. Summary of the invention

[0004] The purpose of the present invention is to provide a modification and regeneration method for waste activated carbon, which solves the problems of poor desulfurization, denitrification and compressive strength existing in the prior art activated carbon.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A method for modifying and regenerating waste activated carbon, the method specifically comprising the following steps:

[0007] S1. Preparation of intermediate material: Wash the waste activated carbon, add copper nitrate solution, mix evenly, and microwave-treat at controlled temperature, filter, take the filter residue, add zinc chloride solution and sodium thiocyanate solution, immerse and shake at room temperature, introduce nitrogen, heat and keep warm to obtain the intermediate material;

[0008] S2. Preparation of modified carbon: steel slag powder and deionized water are mixed and dispersed uniformly and the pH is adjusted, anhydrous ethanol, ferrocene-ethanol solution and intermediate material are added, stirred, filtered, the filter residue is taken, and washed to obtain modified carbon;

[0009] S3. Preparation of finished activated carbon products: uniformly mix the binder, vanadium pentoxide and modified carbon, dry them under controlled temperature, and then roast them to obtain finished activated carbon products.

[0010] As a preferred technical solution of the present invention, the waste activated carbon in step S1 includes any one of waste fruit shell activated carbon and waste coal-based activated carbon.

[0011] Further preferably, the present invention uses waste coal-based activated carbon.

[0012] Furthermore, the waste fruit shell activated carbon includes activated carbon processed with at least one of coconut shell, apricot shell, peach shell, walnut shell, rice husk and date shell as raw materials; the waste coal-based activated carbon includes activated carbon processed with at least one of anthracite, peat, lignite and bituminous coal as raw materials.

[0013] Furthermore, the waste activated carbon has an iodine value of not less than 550 mg / L, a hardness of ≥90%, and an ash content of 5-10%.

[0014] As a preferred technical solution of the present invention, the usage ratio of the waste activated carbon, copper nitrate solution, zinc chloride solution and sodium thiocyanate solution in step S1 is 15-20g:75-100mL:25-35mL:23-30mL.

[0015] As a preferred technical solution of the present invention, the concentration of the copper nitrate solution in step S1 is 0.1 mol / L, the mass fraction of the zinc chloride solution is 40-50%, and the mass fraction of the sodium thiocyanate solution is 20-30%.

[0016] As a preferred technical solution of the present invention, the temperature of the temperature-controlled microwave treatment in step S1 is 23-25°C, and the time is 1-1.5h; the time of the room temperature immersion and oscillation is 8-10h; the heating and insulation is specifically heating to 700-800°C at a heating rate of 8-10°C / min and insulation for 1-1.5h.

[0017] As a preferred technical solution of the present invention, the mass ratio of the steel slag powder, deionized water, anhydrous ethanol, ferrocene-ethanol solution and the intermediate material in step S2 is 0.06-0.065:0.7-0.75:5.5-6:1.1-1.2:1.

[0018] Furthermore, the steel slag powder is ground steel slag powder of 600-700 mesh.

[0019] As a preferred technical solution of the present invention, the pH adjustment in step S2 is to adjust the pH to 6.0 using 1 mol / L hydrochloric acid; the concentration of the ferrocene-ethanol solution is 1 mol / L; the stirring time is 4-5h; and the washing is 3-5 times of washing with anhydrous ethanol.

[0020] As a preferred technical solution of the present invention, the mass ratio of the binder, vanadium pentoxide and modified carbon in step S3 is 1.3-1.5:0.7-0.8:2.8-3.

[0021] Furthermore, the preparation method of the adhesive is: polyvinyl alcohol solution, sodium silicate, deionized water and hydrochloric acid solution are mixed evenly, stirred under temperature control, and then anhydrous borax and polyvinyl acetate are added and mixed evenly to obtain the adhesive.

[0022] Furthermore, the mass ratio of the polyvinyl alcohol solution, sodium silicate, deionized water, hydrochloric acid solution, anhydrous borax and polyvinyl acetate is 4.5-5:0.15-0.2:30-35:1-1.2:0.003-0.0035:0.45-0.5.

[0023] Furthermore, the mass fraction of the polyvinyl alcohol solution is 6-8%; the concentration of the hydrochloric acid solution is 1 mol / L; and the viscosity of the polyvinyl acetate is 7000 mPa·s.

[0024] Furthermore, the temperature of the temperature-controlled stirring is 60-70° C., and the time is 1-2 h.

[0025] As a preferred technical solution of the present invention, the temperature of the temperature-controlled drying in step S3 is 50-55°C; the temperature-controlled roasting is roasting at 600-700°C for 20-30min under a microwave power of 300-400W.

[0026] Beneficial effects of the present invention:

[0027] (1) The present invention uses zinc chloride and sodium thiocyanate to synergistically activate the waste activated carbon, and then compound it with steel slag powder and ferrocene, which effectively increases the adsorption capacity of the obtained activated carbon. Specifically, zinc chloride is used to activate and form pores, and sodium thiocyanate is used to promote the formation of porosity and high specific surface area, thereby increasing the active sites on the surface of the activated carbon, effectively enriching the pollutants near the active sites of the activated carbon; on this basis, steel slag powder containing catalytic manganese oxide and copper oxide components and ferrocene as a solid catalyst are added to assist the system in strengthening and accelerating the adsorption capacity of sulfur dioxide and nitrogen oxides on the surface of the activated carbon, thereby comprehensively improving the desulfurization and denitrification degree of the system.

[0028] (2) The present invention uses sodium silicate and polyvinyl alcohol as main raw materials to prepare a self-made adhesive for the bonding of activated carbon. Due to the presence of sodium silicate and polyvinyl alcohol in the adhesive, a strong network structure is formed; on this basis, polyvinyl acetate is added to increase the strength of the adhesive due to its certain bonding properties; and the added anhydrous borax is embedded in the sodium silicate in the form of boron tetroxide, which further improves the density of the network structure in the system, cross-mixes the adhesive and the activated carbon into a tight whole, retains the pore structure of the activated carbon, does not cause blockage in the pores of the activated carbon, and effectively enhances the compressive strength of the obtained activated carbon.

[0029] (3) The present invention uses waste activated carbon as raw material for modification and regeneration, turning waste into treasure, achieving the recycling of resources and reducing pollution to the environment, which has important practical significance. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] The steel slag powder used in the embodiment of the present invention was purchased from Guilin Hongcheng Mining Equipment Manufacturing Co., Ltd.; no further details will be given later.

[0032] Example 1

[0033] A method for modifying and regenerating waste activated carbon, the method specifically comprising the following steps:

[0034] S1. Preparation of intermediate material: Wash the waste anthracite activated carbon, add 0.1 mol / L copper nitrate solution, mix well, and microwave at 24°C for 1 h, filter, take the filter residue, add 45% zinc chloride solution and 30% sodium thiocyanate solution, immerse and shake at room temperature for 10 h, introduce nitrogen, heat to 800°C at a heating rate of 8°C / min and keep warm for 1 h to obtain the intermediate material;

[0035] The waste anthracite activated carbon has an iodine value of 550 mg / L, a hardness of 92%, and an ash content of 5%;

[0036] The usage ratio of the waste anthracite activated carbon, copper nitrate solution, zinc chloride solution and sodium thiocyanate solution is 15g:75mL:25mL:26mL;

[0037] S2, preparing modified carbon: grind the steel slag powder to 600 mesh and deionized water to mix and disperse evenly, adjust the pH to 6.0 with 1 mol / L hydrochloric acid, add anhydrous ethanol, 1 mol / L ferrocene-ethanol solution and the intermediate material obtained in step S1, stir for 5 hours, filter, take the filter residue, wash it with anhydrous ethanol for 3 times, and obtain modified carbon;

[0038] The mass ratio of the steel slag powder, deionized water, anhydrous ethanol, ferrocene-ethanol solution and intermediate material is 0.06:0.7:5.5:1.1:1;

[0039] S3, preparation of activated carbon product: the binder, vanadium pentoxide and modified carbon were mixed uniformly in a mass ratio of 1.4:0.7:2.8, and then the mixture was dried at 50°C, and then calcined at 650°C for 20 min under a microwave power of 300 W to obtain the activated carbon product;

[0040] The preparation method of the adhesive is as follows: 8% polyvinyl alcohol solution, sodium silicate, deionized water and 1 mol / L hydrochloric acid solution are mixed evenly, the temperature is controlled at 60° C. and stirred for 2 hours, and then anhydrous borax and polyvinyl acetate with a viscosity of 7000 mPa·s are added and mixed evenly to obtain the adhesive;

[0041] The mass ratio of the polyvinyl alcohol solution, sodium silicate, deionized water, hydrochloric acid solution, anhydrous borax and polyvinyl acetate is 4.5:0.15:33:1:0.003:0.45;

[0042] Example 2

[0043] A method for modifying and regenerating waste activated carbon, the method specifically comprising the following steps:

[0044] S1. Preparation of intermediate material: Wash the waste lignite activated carbon, add 0.1 mol / L copper nitrate solution, mix well, and microwave at 23°C for 1 h, filter, take the filter residue, add 40% zinc chloride solution and 20% sodium thiocyanate solution, immerse and shake at room temperature for 8 h, introduce nitrogen, heat to 700°C at a heating rate of 10°C / min and keep warm for 1.5 h to obtain the intermediate material;

[0045] The waste lignite activated carbon has an iodine value of 650 mg / L, a hardness of 90%, and an ash content of 8%;

[0046] The usage ratio of the waste lignite activated carbon, copper nitrate solution, zinc chloride solution and sodium thiocyanate solution is 20g:87mL:35mL:30mL;

[0047] S2, preparing modified carbon: grind the steel slag powder to 600 mesh and deionized water to mix and disperse evenly, adjust the pH to 6.0 with 1 mol / L hydrochloric acid, add anhydrous ethanol, 1 mol / L ferrocene-ethanol solution and the intermediate material obtained in step S1, stir for 4 hours, filter, take the filter residue, wash it with anhydrous ethanol for 4 times, and obtain modified carbon;

[0048] The mass ratio of the steel slag powder, deionized water, anhydrous ethanol, ferrocene-ethanol solution and intermediate material is 0.065:0.75:5.75:1.2:1;

[0049] S3, preparation of activated carbon product: the binder, vanadium pentoxide and modified carbon were mixed uniformly in a mass ratio of 1.3:0.8:3, and then dried at 53°C, and then calcined at 600°C for 30 min under a microwave power of 400 W to obtain the activated carbon product;

[0050] The preparation method of the adhesive is as follows: polyvinyl alcohol solution with a mass fraction of 6%, sodium silicate, deionized water and 1 mol / L hydrochloric acid solution are mixed evenly, the temperature is controlled at 65° C. and stirred for 1 hour, and then anhydrous borax and polyvinyl acetate with a viscosity of 7000 mPa·s are added and mixed evenly to obtain the adhesive;

[0051] The mass ratio of the polyvinyl alcohol solution, sodium silicate, deionized water, hydrochloric acid solution, anhydrous borax and polyvinyl acetate is 5:0.2:30:1.2:0.0035:0.48.

[0052] Example 3

[0053] A method for modifying and regenerating waste activated carbon, the method specifically comprising the following steps:

[0054] S1. Preparation of intermediate material: Wash the waste bituminous activated carbon, add 0.1 mol / L copper nitrate solution, mix well, and microwave at 25°C for 1.5 h, filter, take the filter residue, add 50% zinc chloride solution and 25% sodium thiocyanate solution, immerse and shake at room temperature for 9 h, introduce nitrogen, heat to 750°C at a heating rate of 9°C / min and keep warm for 1.5 h to obtain the intermediate material;

[0055] The waste bituminous coal activated carbon has an iodine value of 600 mg / L, a hardness of 93%, and an ash content of 10%;

[0056] The usage ratio of the waste bituminous coal activated carbon, copper nitrate solution, zinc chloride solution and sodium thiocyanate solution is 18g:100g / mL:30mL:23mL;

[0057] S2, preparing modified carbon: grind the steel slag powder to 700 mesh and deionized water to mix and disperse evenly, adjust the pH to 6.0 with 1 mol / L hydrochloric acid, add anhydrous ethanol, 1 mol / L ferrocene-ethanol solution and the intermediate material obtained in step S1, stir for 4.5h, filter, take the filter residue, wash it with anhydrous ethanol for 5 times, and obtain modified carbon;

[0058] The mass ratio of the steel slag powder, deionized water, anhydrous ethanol, ferrocene-ethanol solution and intermediate material is 0.063:0.72:6:1.15:1;

[0059] S3, preparation of activated carbon product: the binder, vanadium pentoxide and modified carbon were mixed uniformly in a mass ratio of 1.5:0.75:2.9, and then the mixture was dried at 55°C, and then calcined at 700°C for 25 min at a microwave power of 350 W to obtain the activated carbon product;

[0060] The preparation method of the adhesive is as follows: polyvinyl alcohol solution with a mass fraction of 7%, sodium silicate, deionized water and 1 mol / L hydrochloric acid solution are mixed evenly, the temperature is controlled at 70° C. and stirred for 1.5 hours, and then anhydrous borax and polyvinyl acetate with a viscosity of 7000 mPa·s are added and mixed evenly to obtain the adhesive;

[0061] The mass ratio of the polyvinyl alcohol solution, sodium silicate, deionized water, hydrochloric acid solution, anhydrous borax and polyvinyl acetate is 4.8:0.18:35:1.1:0.0033:0.5.

[0062] Comparative Example 1

[0063] Compared with Example 1, the difference is that in step S1 of Comparative Example 1, no zinc chloride solution is added, and the usage ratio of the waste coconut shell activated carbon, the copper nitrate solution and the sodium thiocyanate solution is 15g:75mL:51mL; the remaining operating steps and parameters are the same.

[0064] Comparative Example 2

[0065] Compared with Example 1, the difference is that in step S1 of Comparative Example 2, no sodium thiocyanate solution is added, and the usage ratio of the waste coconut shell activated carbon, the copper nitrate solution and the zinc chloride solution is 15g:75mL:51mL; the remaining operating steps and parameters are the same.

[0066] Comparative Example 3

[0067] Compared with Example 1, the difference is that in step S1 of Comparative Example 3, no steel slag powder is added, and the mass ratio of the deionized water, anhydrous ethanol, ferrocene-ethanol solution and the intermediate material is 0.7:5.5:1.16:1; the remaining operating steps and parameters are the same.

[0068] Comparative Example 4

[0069] Compared with Example 1, the difference is that in step S1 of Comparative Example 4, no ferrocene-ethanol solution is added, and the mass ratio of the steel slag powder, deionized water, anhydrous ethanol and intermediate material is 1.16:0.7:5.5:1; the remaining operating steps and parameters are the same.

[0070] Comparative Example 5

[0071] Compared with Example 1, the difference is that polyvinyl acetate is not added in the adhesive preparation in step S3 of Comparative Example 5, and the other operating steps and parameters are the same.

[0072] Comparative Example 6

[0073] Compared with Example 1, the difference is that no anhydrous borax is added in the adhesive preparation in step S3 of Comparative Example 5, and the other operating steps and parameters are the same.

[0074] Test Example 1

[0075] (1) According to GB / T 30202.4-2013, the desulfurization value of the activated carbon products prepared in Examples 1-3 and Comparative Examples 1-4 was tested, and the results are shown in Table 1.

[0076] (2) According to GB / T 30202.5-2013, the denitration rate of the activated carbon products prepared in Examples 1-3 and Comparative Examples 1-4 was tested. The results are shown in Table 1.

[0077] Table 1

[0078] Desulfurization value (mg / g) Denitrification rate (%) Example 1 60 59 Example 2 58 57 Example 3 58 58 Comparative Example 1 39 48 Comparative Example 2 32 40 Comparative Example 3 36 45 Comparative Example 4 34 42

[0079] As can be seen from Table 1, the activated carbon product prepared by the present invention has an excellent desulfurization and denitrification effect. This is because the present invention uses zinc chloride and sodium thiocyanate to synergistically activate the waste activated carbon, effectively activates and forms pores, and increases the active sites on the surface of the activated carbon. On this basis, it is compounded with steel slag powder and ferrocene, which effectively increases the adsorption capacity of the prepared activated carbon. Therefore, the prepared activated carbon product has an excellent desulfurization and denitrification effect.

[0080] Test Example 2

[0081] According to GB / T 30202.3-2013, the activated carbon products prepared in Examples 1-3 and Comparative Examples 5-6 were subjected to a compressive strength test, and the results are shown in Table 2.

[0082] Table 2

[0083] <![CDATA[Proof pressure (kg / cm 3 )]]> Example 1 42.8 Example 2 41.5 Example 3 42.0 Comparative Example 5 36.1 Comparative Example 6 32.6

[0084] As can be seen from Table 2, the finished activated carbon product prepared by the present invention has outstanding compressive strength. This is because the present invention uses sodium silicate and polyvinyl alcohol as the main raw materials to make a self-made adhesive for the bonding of activated carbon, a strong network structure is formed in the system, polyvinyl acetate is added on this basis, and its certain bonding property increases the strength of the prepared adhesive, anhydrous borax is added, which is embedded in the sodium silicate in the form of boron oxide, further improving the density of the network structure in the system, cross-mixing the adhesive and the activated carbon into a tight whole, retaining the pore structure of the activated carbon, not causing blockage in the pores of the activated carbon, and effectively enhancing the compressive strength of the obtained activated carbon.

[0085] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0086] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for modifying and regenerating waste activated carbon, characterized in that: The method specifically comprises the following steps: S1. Preparation of intermediate material: Wash the waste activated carbon, add copper nitrate solution, mix evenly, and microwave-treat at controlled temperature, filter, take the filter residue, add zinc chloride solution and sodium thiocyanate solution, immerse and shake at room temperature, introduce nitrogen, heat and keep warm to obtain the intermediate material; S2. Preparation of modified carbon: steel slag powder and deionized water are mixed and dispersed uniformly and the pH is adjusted, anhydrous ethanol, ferrocene-ethanol solution and intermediate material are added, stirred, filtered, the filter residue is taken, and washed to obtain modified carbon; S3, preparing the finished activated carbon product: mixing the binder, vanadium pentoxide and modified carbon uniformly, drying under controlled temperature, and then roasting to obtain the finished activated carbon product; The preparation method of the adhesive is as follows: polyvinyl alcohol solution, sodium silicate, deionized water and hydrochloric acid solution are mixed evenly, the mixture is stirred under controlled temperature, and then anhydrous borax and polyvinyl acetate are added and mixed evenly to obtain the adhesive; The mass ratio of the polyvinyl alcohol solution, sodium silicate, deionized water, hydrochloric acid solution, anhydrous borax and polyvinyl acetate is (4.5-5): (0.15-0.2): (30-35): (1-1.2): (0.003-0.0035): (0.45-0.5); Step S1: the temperature of the temperature-controlled microwave treatment is 23-25°C, and the time is 1-1.5h; the time of the room temperature immersion and oscillation is 8-10h; the heating and heat preservation is specifically heating to 700-800°C at a heating rate of 8-10°C / min and keeping warm for 1-1.5h; The temperature of the temperature-controlled drying in step S3 is 50-55°C; the calcination is carried out at a temperature of 600-700°C for 20-30 minutes under a microwave power of 300-400W; The mass ratio of the binder, vanadium pentoxide and modified carbon in step S3 is (1.3-1.5): (0.7-0.8): (2.8-3).

2. The method for modifying and regenerating waste activated carbon according to claim 1, characterized in that: The waste activated carbon in step S1 includes any one of waste fruit shell activated carbon and waste coal-based activated carbon.

3. The method for modifying and regenerating waste activated carbon according to claim 1, characterized in that: The usage ratio of the waste activated carbon, copper nitrate solution, zinc chloride solution and sodium thiocyanate solution in step S1 is 15-20 g: 75-100 mL: 25-35 mL: 23-30 mL.

4. The method for modifying and regenerating waste activated carbon according to claim 1, characterized in that: The mass ratio of the steel slag powder, deionized water, anhydrous ethanol, ferrocene-ethanol solution and the intermediate material in step S2 is (0.06-0.065): (0.7-0.75): (5.5-6): (1.1-1.2):

1.

5. The method for modifying and regenerating waste activated carbon according to claim 1, characterized in that: The pH adjustment in step S2 is to adjust the pH to 6.0 using 1 mol / L hydrochloric acid; the concentration of the ferrocene-ethanol solution is 1 mol / L; the stirring time in step S2 is 4-5 hours; and the washing is 3-5 times of washing with anhydrous ethanol.

Citation Information

Patent Citations

  • Active carbon used for adsorbing and removing sulfides in gasoline, and preparation method thereof

    CN102188954A

  • Preparation method and application of ammonium thiocyanate modified activated carbon

    CN109574008A

  • Preparation process for active regeneration of waste activated carbon

    CN116474749A

  • Low-cost anti-scaling efficient flue gas desulfurizer and preparation method thereof

    CN117815872A